Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di SDIT Ibnul Qayyim Makassar (Journal of Gurutta Education, 2022)
One of the effective forces that determine the success of a school or educational institution in achieving its goals is the leadership of the principal. The principal is one of the components of education that has the most role in improving the quality of education. Quality education refers to a quality education. The purpose of this study was to find out how the role of the principal's leadership at SDIT Ibnul Qayyim Makassar in improving the quality of education at the school. The research method used is qualitative research with a descriptive approach. The subjects in this research are the Principal, Deputy Principal, SDIT Ibnul Qayyim educators and the data collection methods are observation, interviews, documentation and triangulation. Data analysis went through three stages, namely data reduction, data presentation, and verification. The results of this study indicate that the role of the SDIT IQIS principal has been very good as evidenced by the programs that have been carried out in an effort to improve the quality of the curriculum, the learning process, the quality of students, the quality of teachers and education staff.